Mining for facts: PacRim Cayman LLC v. El Salvador - Alexandre de Gramont (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2010)
Responds to Perspective No. 23 by Gus Van Harten by briefly presenting Pacific Rim's case in Pacific Rim v. El Salvador and defends the international arbitration process by which this case is being adjudicated as fair, neutral and objective for both parties.
Keywords: 330